PENERAPAN ETIKA BISNIS ISLAM DALAM TRANSAKSI E-COMMERCE - Neli Purwanti; Ajeng Pujawati (STAI Sebelas April Sumedang, 2021)
E-commerce transactions or often referred to as buying and selling online, namely buying and selling made by sellers and buyers through the internet, where the seller and buyer do not meet each other. One of the social media used to sell goods is Instagram social media. Buying and selling online is increasingly crowded because it makes it easier for sellers to market their merchandise, and also makes it easier for buyers to find what they need. But in practice there are still sellers who commit fraud. From this background the problem formulation can be drawn: 1) How is the application of Islamic business ethics in e-commerce transactions to sellers of Instagram social media users, 2) How is the trend of the application of Islamic business ethics in e-commerce transactions to sellers of Instagram social media users, 3 ) What are the supporting and inhibiting factors in the application of Islamic business ethics in e-commerce transactions to sellers of Instagram social media users. This research is a case study research using a qualitative approach by collecting data through observation, interviews and documentation. Analysis of the data used by data reduction, data presentation and verification. In this thesis the conclusion that sellers of Instagram social media users have not fully implemented Islamic business ethics. There are still some that are lacking in the application of business ethics